Genetic variability within Adenosine Deaminase gene and uterine leiomyomas. (April 2016) - Gloria-Bottini, Fulvia; Saccucci, Patrizia; Ammendola, Maria; Neri, Anna; Magrini, Andrea; Bottini, Egidio
Abstract: Objective: The recent observation of an association of colon cancer with two polymorphic sites within the Adenosine Deaminase (ADA) gene suggests an involvement of these polymorphisms in the development of solid tumors. This prompted us to search for a similar association in uterine leiomyomas. Study design: We have studied 181 women admitted to the hospital for leiomyomas requiring surgical intervention and 248 women of comparable age without clinical signs of leiomyomas. All women were from the White population of Rome and gave verbal consent to participate in the study. The genotypes of three polymorphic sites (ADA1, ADA2, ADA6 ) of ADA gene were determined by DNA analysis. Results: A higher proportion of ADA2 *1/*1 genotype and of carriers of the ADA6 *1 allele was observed in women with leiomyomas as compared to controls. This parallels the association found in colon cancer. Conclusions: This pattern is identical to that previously observed in colon cancer making the possibility of mere sample chance artifact unlikely and supporting the hypothesis that genetic polymorphisms within the ADA gene could be involved in the susceptibility to solid tumors. Genetic variability within the ADA gene may influence adenosine concentration and in turn the immune response by lymphocytes in solid tumors. On the other hand ADA molecules acting as ecto-enzyme may be involved in the transduction of signals in the cell surface with important effects on tumor development.